Comparative Analysis of Interface Layout Design of Educational Web Sites in China and Korea (Asian Journal of Social Science Studies, 2021)
Taking design of educational websites as an example, this paper analyzes the basic elements of interface design, including composition, user research and theme practice, and compares the similarities and differences between Chinese and Korean web designs from four perspectives: text, image, color and navigation design, respectively. According to the comparison results, both countries' educational web designs prefer to use calligraphic fonts, but China prefers square diagrams, horizontal and vertical navigation, and stable and prudent colors, while Korean designs tend to use circular diagrams, tilted navigation, and youthful and lively colors. This paper provides reference for China's educational web design innovation by comparing the similarities and differences of the two countries' designs.